MEMAKSIMALKAN SASARAN HUMAS DI LEMBAGA PENDIDIKAN - Okta Fakhrurizae (IAIN Purwokerto, 2019)
Management of institutional relations with the community is the process of managing communication from planning activities to controlling the process and the results of its activities. Community involvement in the field of education is an effort to empower the community in the development of the field of education which means to involve the community in planning, implementation and supervision of education. The vision of public relations in educational institutions to create a good image for educational institutions. The target of public relations in educational institutions is seen from the target as an object and a goal of the public relations. Targets as an objects are internal objects including students, teachers, and education personnel, while external objects include student guardians, the community, and mass media. Without assistance from the community, an educational institution cannot function properly and without a good program the educational institution will fail to achieve its goals. To maximize the goals of public relations, it is necessary to have techniques in dealing with the community including: 1) Home visits, 2) open houses, 3) school exhibitions, 4) school magazines.